Consumo de hipoglucemiantes dispensados en una botica privada del distrito de Trujillo, febrero 2018 - enero 2019 - Loyola Varas, Denia Elizabeth (2019)
This report on pre-professional practices was carried out with the purpose of evaluating the consumption of hypoglycaemic drugs dispensed in a private pharmaceutical establishment of the district of Trujillo between February 2018 and January 2019; the hypoglycemic agents Januvia 100 mg, Glucophage XR 500 mg and Glicenex 850 mg were considered, as they are in greatest demand. The consumption was evaluated using the international technical unit of measurement Defined Daily Dose per thousand inhabitants per day (DHD), which is an international technical unit for measuring the consumption of medicines in a population. The results showed that Januvia was the hypoglycaemic with the highest consumption during the year with 2.76 DHD/1000hb/d; followed by Glicenex with 1.17 DHD/1000hb/d and Glucophage XR 500 mg with 0.69 DHD/1000hb/d. It was also determined that Januvia 100 mg generated higher cost in the month of December with S / 401.00 corresponding to the sale of 45 units, on the other hand Glucophage XR 500 mg generated a higher cost in the month of August S / 98.00 with 39 units and Glicenex 850 mg S / 59.00 in the month of January with 39 units. Januvia 100 mg was the hypoglycemic agent with the highest annual cost of S / 3, 035.00. Although there is a positive trend in the consumption of Januvia 100 mg, Glucophage XR 500 mg and Glicenex 850 mg, over time, this is not statistically significant (p = 0.2547, p = 0.6418 and p = 0.1992).